The Effect of Interest Rates on Distribution and Banking Credit Loans - Risdani Mu'arif; Arfigo Yahya; Chairina (Experimental Student Experiences, 2022)
The purpose of this essay is to outline the implications of interest rate vulnerability on bank credit terms and conditions. The data collection method used is a qualitative case study model. It can be concluded from the literature used as the basis of this study that the impact of interest rates on bank loan default rates is very significant. This situation is in line with the rules of the lending process, specifically that a credit crunch will make it difficult for people to obtain credit. It is hoped that the findings of this investigation will assist the bank's management team and community groups wishing to carry out further investigations. In general, every research has drawbacks and problems; as a result, researchers can continue their work by modifying their variables or samples.